Consumers’ Perceptual Experiences of the Prices and their Relevance to Brand Image and Brand Loyalty - Siti Fathia Khairunnisa (Jobmark: Journal of Branding and Marketing Communication, 2024)
How consumers perceive a price is believed to have certain value has become the focus of firm strategies in recent years. This study explores on how Consumers’ Perceptual Experiences of the Prices and their Relevance to Brand Image and Brand Loyalty. The findings suggest that price is not the main star of the price itself. There are so many things revolving around price that have relevance with Brand Image & Brand Loyalty. This research found that customers memorize prices better when they have a good experience with the price & memorize it as a positive memory and it locks the image of a good-quality brand with good-quality price for their subjective affordability. This thesis also creates several follow-up questions as this thesis found, information received by customers affects the way they justify a price, several questions are then created such as what kind of communication is the most effective in communicating added value or what kind of information can justify added value.